DEVELOPMENT AND IMPROVEMENT OF KURASH SPORT - Achilov Telman Sadullayevich (Modern American Journals, 2025)
Brief information about the types of wrestling and their development and progress.
Keywords: Sport, struggle, world, pride, independence, arena, coach, method, work.